Na+/K+-pump and neurotransmitter membrane receptors - Pivovarov, Arkady S.; Calahorro, Fernando; Walker, Robert J. (Invertebrate neuroscience, 2019)
Na + /K + -pump is an electrogenic transmembrane ATPase located in the outer plasma membrane of cells. The Na + /K + -ATPase pumps 3 sodium ions out of cells while pumping 2 potassium ions into cells. Both cations move against their concentration gradients. This enzyme’s electrogenic nature means that it has a chronic role in stabilizing the resting membrane potential of the cell, in regulating the cell volume and in the signal transduction of the cell. This review will mainly consider the role of the Na + /K + -pump in neurons, with an emphasis on its role in modulating neurotransmitter receptor. Most of the literature on the modulation of neurotransmitter receptors refers to the situation in the mammalian nervous system, but the position is likely to be similar in most, if not all, invertebrate nervous systems.